Homologated propagation models for classical channel in FSO-QKD systems - López-Leyva, Josué Aarón; Talamante, Ariana; Ponce Camacho, Miguel Ángel; Castaeda, Mario; Arvizu Mondragón, Arturo; Santos-Aguilar, Joel; Ramos-García, Raúl (My University, 2018)
In this paper, the performance of a QKD system emulated by means of experimental C&DH and Communications subsystems of a CubeSat using a novel proposed technique based on the homologation of propagation models using COTS devices for the classical channel is presented. This technique does not require the spacecraft to be in its final orbit and it is based on the experimental performance of the aforementioned subsystems using the two-ray propagation model. The principal advantage of the technique used is the calculus of the Final Secret Key Rate (FSecKR) considering a different testing condition, i.e., without launching the CubeSat into the final orbits nor using an aircraft as launching emulator. The final results show that the FSecKR can be emulated for the free space propagation model considering the overall performance in the two-ray propagation model.
Keywords: Space vehicles; Aircraft; CubeSat; Mathematical model; Aerospace electronics; Antenna measurements; Campus Ensenada